2019
DOI: 10.3390/app9163317
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Non-Sustainable Soil Erosion Rates in the Tierra de Barros Vineyards (Extremadura, Spain) Using an ISUM Update

Abstract: Monitoring soil erosion processes and measuring soil and water yields allow supplying key information to achieve land degradation neutrality challenges. Vineyards are one of the most affected agricultural territories by soil erosion due to human and natural factors. However, the spatial variability of soil erosion, the number of sampling points, and plot size necessary to estimate accurate soil erosion rates remains unclear. In this research, we determine how many inter-rows should be surveyed to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…In the past, soil loss and surface runoff have also been studied using different plot sizes by researchers in other countries investigating vineyards (Rodrigo-Comino et al, 2019) and other land uses, such as grasslands and subtropical environments (Thomaz and Vestena, 2012;Mayerhofer et al, 2017). We have reported that runoff on a small plot was about 30% higher in our experiments than on large plots, but that the soil loss was approximately the same for small and large plots under natural rainfall.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the past, soil loss and surface runoff have also been studied using different plot sizes by researchers in other countries investigating vineyards (Rodrigo-Comino et al, 2019) and other land uses, such as grasslands and subtropical environments (Thomaz and Vestena, 2012;Mayerhofer et al, 2017). We have reported that runoff on a small plot was about 30% higher in our experiments than on large plots, but that the soil loss was approximately the same for small and large plots under natural rainfall.…”
Section: Discussionmentioning
confidence: 61%
“…It is clear that different results might be obtained when the plot size increases. In vineyards, tests were recently carried out by Rodrigo-Comino et al (2019) using ISUM (Improved Stock Unearthing Method) in the viticultural area of Tierra de Barros (Extremadura, Spain). The authors demonstrated that measurements of soil loss on plots from 300 to 900 m 2 in size, may result in differences of about 3 t ha −1 yr −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has suggested that soil loss in vineyards is above the level that amounts to tolerable soil loss, less so for older vineyards with more organic matter content and higher bulk density in relation to younger vineyards [125] Moreover, accurately measuring soil loss in vineyards is fraught with difficulties, because different methodologies available tend to give different results. Thus, there is a need to improve the accuracy of measurements [126]. However, research has shown that there are various practices to mitigate the effects of soil erosion such as terracing, sediment fences, check dams, grass margins, contour farming, and the use of cover crops [127,128].…”
Section: (Un)sustainable Agronomic Management and Resulting Soil Lossmentioning
confidence: 99%
“…Accurately monitoring soil erosion processes and measuring soil and water yields can provide key information for achieving land-degradation neutrality. For example, Rodrigo-Comino [17] considers vineyards to be one of the agricultural areas most subject to human and natural factors. However, the spatial variability of soil erosion, the number of sampling points, and the size of the plot required to accurately estimate soil erosion rates remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the spatial variability of soil erosion, the number of sampling points, and the size of the plot required to accurately estimate soil erosion rates remain unclear. In view of this, Rodrigo-Comino [17] used the improved stock unearthing method (ISUM) to analyze the soil erosion rate of Tierra de Barros (Extremadura, Spain). The results of the study found that the spatial differences in soil erosion were small, and the differences between rows were not statistically significant.…”
Section: Introductionmentioning
confidence: 99%